AB0067 Vascular endothelial growth factor (vegf) and its receptors in rheumatoid arthritis and osteoarthritis. (1st June 2001) - Fink, B; Böttcher, A; Schwarloh, B; Fuerst, M; Hansen-Algenstaedt, N; Rüther, W; Algenstaedt, P
Abstract : Background: Rheumatoid arthritis (RA) is characterised by synovial proliferation. Tissue proliferation in general is known to be dependent on sufficient oxygen and nutrition supply. Therefore angiogenesis, the process of new vessel formation, is considered to play a crucial role not only for tumour growth but also in rheumatoid arthritis. The angiogenetic process is regulated by several cytocines. Most important factor is the Vascular Endothelial Growth Factor (VEGF) and its cognate receptors KDR and FLT-1, known to be regulated by hypoxia as well as inflammatory cytocines. On the other hand RA is a chronic inflammatory process. Objectives: The aim of this study was to investigate whether the angiogentic process in RA is a local versus a systemic effect. Methods: Synovial tissue was taken during total knee replacement from 20 patients with RA and 20 patients with osteoarthritis (OA). Expression of VEGF, KDR and FLT-1 mRNA was analysed quantitatively using real-time PCR (Light-Cycler). Moreover in these patients plasma level of VEGF was examined using ELISA. Results: VEGF and FLT-1 were detected in the synovial tissue of all RA- and OA-patients. The levels were significantly higher in patients with RA compared to OA. KDR was established in 60% of RA and 25% of OA. Plasma level of VEGF was increased in 100% of the RA-patients and in 60% of the OA-patients. Conclusion: VEGF and its cognate receptors are significantly higher expressed in synovial tissue of patients with rheumatoid arthritis. Increased expression levels in patients with osteoarthritis might be due to reactive inflammatory synovitis. Therefore antiangiogenitic therapy might be useful not only in rheumatoid arthritis but also in reactive inflammatory arthritis. Significantly increased VEGF-plasma-levels in patients with rheumatoid arthritis may explain the benefit of a systemic, versus a local anti-angiogentic therapy.